Correlação entre a presença do polimorfismo Ala D2 da enzima Desiodase tipo 2 (Dio2) e a funcionalidade de indivíduos com transtorno do espectro do autismo - Gomez, Thiago Gnecco Bueno (2017)
The presence of the Thr92Ala-D2 polymorphism in homozygous individuals seems related to the increase of cellular oxidative stress, although it does not phenotypic alterations, suggesting the existence of compensatory mechanisms. The hypothesis of our study considered the possibility that in individuals with compensatory mechanisms are not sufficient and the presence of of the polymorphism may lead to changes in the behavior of these patients. Therefore, we studied 97 individuals diagnosed with ASD and followed up In the Center for Integrated Mental Health Care (CAISM). All patients were evaluated by the Vineland Adaptive Behavior Scale, 2nd The Autism Behavior Checklist and were genotyped for the Thr92Ala-D2 polymorphism by extracting DNA from the buccal epithelium. For all statistical analyzes, the one-way ANOVA test with Tukey's test was used to analyze the genotypes separately. Our results show that the presence of Thr92Ala-D2 polymorphism in homozygotes improves the functionality of autistic individuals in the subdomains of Communication, Language, Daily Activities and Adaptive Level. In addition, the presence of 92Ala-D2 allele appears to exert a dose-dependent effect, since When present in heterozygosity the score presents intermediate values Between polymorphic homozygous (AA) and non-homozygous individuals Polymorphic (TT). The data obtained were exactly opposite to our hypothesis Initial. The literature describes changes in the pathways of ubiquitination and Neuregulin 1 in typical individuals with the polymorphism. This could explain the Autism, since these two pathways may be Involved in the TEA phenotype. In conclusion, the present study shows that Presence of the Thr92Ala-D2 polymorphism in homozygous Functionality in communication, daily activities, social aspects, general level adaptation in individuals with ASD.